Growth and feed utilization of Boer x Kacang crossbred goats offered total mixed rations of different protein and energy levels - Simon P. Ginting; Kiston Simanihuruk; Antonius Antonius; Andi Tarigan (Indonesian Center for Animal Research and Development (ICARD), 2017)
The aim of this study was to evaluate the growth of and feed utilization by Boer x Kacang crosses goats fed on total mixed ration differing in protein and energy levels. Four total mixed rations combination were formulated to contain 16 and 18% crude protein and 2650 and 2850 Kcal ME/ kg DM (dried matter) energy density. Twenty-eight male Boer x Kacang crosses goats (14.5 ± 1.14 kg) and of age ranging from 4 to 5 months were randomly allocated to one of these four TMRs (total mixed rations) (7 animals/TMR). The effects of dietary treatment were assessed using the general linear model and significance of the diet effects was detected using Duncan’s multiple range test. Dry matter intake increased as metabolizable energy density of diet increased from 2650 to 2850 Kcal/kg DM, but it is not affected by increasing crude protein level from 16 to 18%. The average daily gains were not improved (P>0.05) as the crude protein levels and metabolizable energy density of diet increased. Crude protein levels and ME density did not affect (P>0.05) the DM, OM and energy digestibility, but NDF digestibility was affected by the ME density of diets (P<0.05). Daily N intakes were greater (P<0.0%) in goats received diets higher in the crude protein and metabolizable energy levels. At this high rate of feed intake this type of goats are able to gain optimally when offered feed with crude protein level of 16% and metabolizable energy density of 2850 Kcal/kg DM.